Use of wheat bran arabinoxylans in chitosan-based films : effect on physicochemical properties - Costa, Maria J. (2015)
The aim of this work was to evaluate physicochemical properties of chitosan-based films with different fractions of arabinoxylans (AXs). Five fractions composed by AXs or mixtures of AXs and arabino-xylo-oligosaccharides (AXOS) obtained through three different processes were added to chitosan-based films. These films were obtained by solvent casting and characterized in terms of water vapor permeability (WVP), opacity, thickness, moisture content and mechanical properties (i.e., tensile strength TS and elongation at break EB), being the chemical interactions evaluated by FTIR. Moisture content values ranged between 20 and 30% for all five studied films being the lowest value observed for chitosan films with the fraction F1 of AX/AXOS (21.1%). The films with incorporation of F3a, F3b and F4 AXs fraction were more opaque (>10%) than the other studied films. Regarding mechanical properties CH films presented EB and TS values of 31.26% and 8.25 MPa, respectively, both these values remain statistically equal with the incorporation of AX/AXOS except for films containing the fraction F1 and F2. For films with the F2 fraction were obtained higher values of EB (41.31%) while for CH films containing the F1 fraction the TS values (13.07 MPa) increased. In conclusion, wheat bran AXs can be successfully incorporated into chitosan-based edible films pro-viding, together with chitosan, an extra functional value to films, due their health benefits.